POST TRAUMATIC STRESS DISORDERS (PTSD) WITH SEVERE DEPRESSION SYMPTOMS WITH ACUTE PSYCHOTIC IN PATIENT WITH HISTORY AS A PEDOPHILE VICTIMS AND DOMESTIC VIOLENCE IN 22 YEARS OLD MAN : A CASE REPORT - I Ketut Agus Indra Adhiputra (E-Jurnal Medika Udayana, 2014)
Post traumatic stress disorders (PTSD) is a disorder that is fairly common in thecommunity. Every event in the life will have its own meaning in later, especially eventsthat occur in childhood. Data in the U.S. showed 60% men and 50% women have atraumatic experience, which develops into PTSD approximately 6.7% of the entirepopulation. While data from the Indonesian National Commission of Women, since 20072010there has been 91311 cases of sexual violence against women, as well as cases ofchild sexual abuse reported to reach 250 cases. Presenting symptoms can range fromanxiety disorders, depression, until psychotic. The severity of symptoms depends on eachself-defense mechanism thus the PTSD symptoms are very diverse.